2008
DOI: 10.1111/j.1467-9531.2008.00198.x
|View full text |Cite
|
Sign up to set email alerts
|

8. Outliers, Leverage Observations, and Influential Cases in Factor Analysis: Using Robust Procedures to Minimize Their Effect

Abstract: Parallel to the development in regression diagnosis, this paper defines good and bad leverage observations in factor analysis. Outliers are observations that deviate from the factor model, not from the center of the data cloud. The effects of each kind of outlying observations on the normal distribution-based maximum likelihood estimator and the associated likelihood ratio statistic are studied through analysis. The distinction between outliers and leverage observations also clarifies the roles of three robust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
106
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(109 citation statements)
references
References 30 publications
(74 reference statements)
3
106
0
Order By: Relevance
“…In the context of SEM, the development of cases-influence diagnostics remains an open area of research. Some caseinfluence diagnostic methods are based on case-level residual estimates (Bollen & Arminger, 1991;Yuan & Hayashi, 2010;Yuan & Zhong, 2008) and others are based on local influence analysis (Lee & Wang, 1996). With PP-PPMC, we show that the approach as outlined for global model fit assessment can be adapted to automate the generation of p values and plots useful for case-influence diagnosis for any appropriately defined test quantity.…”
Section: Poor Person's Ppmc For Case Diagnosticsmentioning
confidence: 98%
See 3 more Smart Citations
“…In the context of SEM, the development of cases-influence diagnostics remains an open area of research. Some caseinfluence diagnostic methods are based on case-level residual estimates (Bollen & Arminger, 1991;Yuan & Hayashi, 2010;Yuan & Zhong, 2008) and others are based on local influence analysis (Lee & Wang, 1996). With PP-PPMC, we show that the approach as outlined for global model fit assessment can be adapted to automate the generation of p values and plots useful for case-influence diagnosis for any appropriately defined test quantity.…”
Section: Poor Person's Ppmc For Case Diagnosticsmentioning
confidence: 98%
“…In the context of factor analysis models, Yuan and Zhong (2008) showed that similar classifications of influential cases are possible when the factor analysis model is regarded as a multivariate regression model with the factor scores playing the role of the predictors and the observed variables playing the role of responses. Outliers and leverage points can then be defined using estimates of factor scores and residuals.…”
Section: Lee Cai Kuhfeldmentioning
confidence: 99%
See 2 more Smart Citations
“…Multivariate analyses have also been enriched by robust statistics. Factor analysis [21] , structural equation modeling [22,23] , and linear mixedeffects models, for both hierarchical and crossed structures [24][25][26] , can also be estimated within the robust framework.…”
Section: Robust Statisticsmentioning
confidence: 99%